Under-Reporting of COVID-19 Cases Among Indigenous Peoples in Brazil: A New Expression of Old Inequalities - Fellows, Martha; Paye, Valéria; Alencar, Ane; Nicácio, Mário; Castro, Isabel; Coelho, Maria Emília; Silva, Camila V. J.; Bandeira, Matheus; Lourival, Reinaldo; Basta, Paulo Cesar (Frontiers in Psychiatry, 2021)
Objective: To estimate the incidence, mortality, and lethality rates of COVID-19 among Indigenous Peoples in the Brazilian Amazon. Additionally, to analyze how external threats can contribute to spread of the disease in Indigenous Lands (IL). Methods: The Brazilian Amazon is home to nearly half a million Indigenous persons, representing more than 170 ethnic groups. As a pioneer in heading Indigenous community-based surveillance (I-CBS) in Brazil, the Coordination of the Indigenous Organizations of the Brazilian Amazon (COIAB) started to monitor Indigenous COVID-19 cases in March of 2020. Brazil’s Ministry of Health (MOH) was the main source of data regarding non-Indigenous cases and deaths; to contrast the government’s tally, we used the information collected by I-CBS covering 25 Special Indigenous Sanitary Districts (DSEI) in the Brazilian Amazon. The incidence and mortality rates of COVID-19 were calculated using the total number of new cases and deaths accumulated between the 9th and 40th epidemiological weeks. We studied (a) the availability of health care facilities to attend to Indigenous Peoples; (b) illegal mines, land grabbing, and deforestation to perform a geospatial analysis to assess how external threats affect Indigenous incidence and mortality rates. We used the Generalized Linear Model (GLM) with Poisson regression to show the results. Results: MOH registered 22,127 cases and 330 deaths, while COIAB’s survey recorded 25,356 confirmed cases and 670 deaths, indicating an under-reporting of 14% and 103%, respectively. Likewise, the incidence and mortality rates were 136% and 110% higher among Indigenous when compared with the national average. In terms of mortality, the most critical DSEIs were Alto Rio Solimões, Cuiabá, Xavante, Vilhena and Kaiapó do Pará. The GLM model reveals a direct correlation between deforestation, land grabbing and mining, and the incidence of cases among the Indigenous. Conclusion: Through this investigation, it was possible to verify that not only the incidence and mortality rates due to COVID-19 among Indigenous Peoples are higher than those observed in the general population, but also that the data presented by the federal government are underreported. Additionally, it was evident that the presence of illegal economic activities increased the risk of spreading COVID-19 in ILs.